Integrating Islamic Pedagogy and The Sustainable Development Goals in Preparing Future Educators in Uzbekistan - Dustnazar Omonovich Khimmataliev; Muqaddas Qahramonovna Rahmonova; Ruzimurat Kungratovich Choriev; Xalikova Nargiza Abduvaliyevna; Nilufar Parda Qizi Omonova; Barno Tajimovna Badalova; Gulasal Abdukunduzovna Berdalieva (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
The development of students’ creative competence is a critical aspect of preparing future educators, particularly within the framework of Islamic education. This study investigates how the integration of Islamic religious education principles with the Sustainable Development Goals (SDGs) enhances students’ professional and pedagogical readiness in higher education. Employing a qualitative approach, the research involved observing pedagogical practices, analysing the curriculum, and evaluating educational outcomes across selected Islamic universities. The results revealed that incorporating Islamic educational values into learning processes nurtured creativity while fostering ethical awareness and sustainability-oriented thinking. The SDGs served as a global reference to contextualize innovation in teaching, while Islamic values grounded the process in moral and spiritual development. Students showed notable improvement in critical thinking, cultural sensitivity, and adaptability, skills essential for professional practice in dynamic educational environments. This study emphasizes the importance of holistic educational models that integrate Islamic ethical frameworks and global sustainability agendas to foster creative, responsible, and future-ready educators. The findings suggest that integrating spiritual, ethical, and sustainable perspectives into curriculum design can significantly contribute to the advancement of Islamic education in higher education institutions.